2016
DOI: 10.1016/j.jash.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of sodium intake on uric acid and blood pressure and their causal implication

Abstract: Reducing uric acid is hypothesized to lower blood pressure, although evidence is inconsistent. In this ancillary of the DASH-Sodium trial, we examined whether sodium-induced changes in serum uric acid (SUA) were associated with changes in blood pressure. One hundred and three adults with pre- or stage 1 hypertension, were randomly assigned to receive either the DASH diet or a control diet (typical of the average American diet) and were fed each of 3 sodium levels (low, medium, and high) for 30 days in random o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 52 publications
(51 reference statements)
2
17
0
Order By: Relevance
“…A total of 47 dietary salt studies met the inclusion criteria: Six meta‐analyses, six RCTs, 11 prospective cohort studies, two retrospective cohort studies, 20 cross‐sectional studies and two case‐control studies, two post hoc analyses of RCTs. The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 47 dietary salt studies met the inclusion criteria: Six meta‐analyses, six RCTs, 11 prospective cohort studies, two retrospective cohort studies, 20 cross‐sectional studies and two case‐control studies, two post hoc analyses of RCTs. The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers .…”
Section: Resultsmentioning
confidence: 99%
“…Of 47 identified studies, eight met the inclusion criteria for outcomes examined and methodological quality and thus were included in the detailed risk of bias assessments and critical appraisals: Two meta‐analyses, one RCT, four prospective cohort studies, and one post hoc analysis of two RCTs . The studies found that: Dietary modifications, including low sodium diets, are associated with a variable reduction in BP; dietary sodium modification did not affect BP in normotensive individuals; medium‐high sodium intake in combination with the DASH diet lowered BP and uric acid levels in pre‐stage or stage 1 hypertensive individuals compared to a control diet; sodium excretion is not associated with risk of CKD; healthy dietary patterns reduce risk of major renal outcomes (composite of death due to renal causes and dialysis, with death due to a nonrenal cause); higher sodium excretion was associated with an increased risk of CVD in individuals with CKD; higher sodium excretion was associated with increased risk of mortality in pre‐hypertensive adults; a low sodium diet is associated with improved markers of kidney function in individuals with autosomal dominant polycystic kidney disease (ADPKD) . Therefore, most of these high‐quality studies (n = 5) found adverse effects of excess sodium on health outcomes; one study reported the benefits of sodium restriction on BP and two studies reported neutral results.…”
Section: Resultsmentioning
confidence: 99%
“…Another trial performed in 27 men showed that increasing sodium intake from 20 mEq/day to 200 mEq/day decreased UA levels by 1 mg/dL 33 . In addition, a randomized crossover trial of 103 adults with prehypertension or stage I hypertension showed that 30 days of low versus high sodium intake (60 versus 180 mmol/day) significantly decreased serum UA 18 , 19 . In this study, we showed that the serum UA levels were similar between each quartile of estimated sodium excretion in prehypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 found that serum UA could predict not only short-term but also long-term incidence of cardiovascular events as well as cardiovascular death and all-cause mortality. Recent studies have shown that increased sodium intake significantly lowers serum UA 18 , 19 . However, no research has focused on the relationship between dietary salt intake and UA levels, especially urinary UA excretion, in prehypertensive participants.…”
Section: Introductionmentioning
confidence: 99%
“…37 Regarding the association with BP, another study reported that sodium intake was significantly associated with uric acid and BP in opposite directions. 40 The increase in sodium intake was associated with lower uric acid and higher BP. These findings suggest that uric acid is unlikely to mediate changes in BP in the context of dietary sodium intake.…”
Section: Novel Biologymentioning
confidence: 96%